2004
DOI: 10.1021/ja0450408
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Peptide Backbone Modifications in an α-Helical Coiled Coil

Abstract: In this paper, we present 1,2,3-triazole epsilon2-amino acids incorporated as a dipeptide surrogate at three positions in the sequence of a known alpha-helical coiled coil. Biophysical characterization indicates that the modified peptides retain much of the helical structure of the parent sequence, and that the thermodynamic stability of the coiled coil depends on the position of the incorporation of the epsilon-residue. Crystal structures obtained for each peptide give insight into the chemical behavior and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
256
0
15

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(276 citation statements)
references
References 17 publications
5
256
0
15
Order By: Relevance
“…In addition, successful replacement of two amino acids in a-helical peptides by a triazole unit has been shown to not significantly influence the secondary peptide structure. 20 To date the triazole linkage has scarcely been used for peptidesteroid conjugation and only to assemble short apolar tripeptides onto bile acid scaffolds, 24 despite the increasing interest of these type of conjugates in diverse applications such as HIV inhibitors 25,26 and immunogens for vaccine development. 27 In the current work we have designed and synthesized four different scaffolds for peptide dimerization of the GCN4 basic region, which was made possible by optimizing conditions for the CuAAC mediated conjugation of the long, unprotected and functionalized zipper peptides.…”
Section: Q4mentioning
confidence: 99%
“…In addition, successful replacement of two amino acids in a-helical peptides by a triazole unit has been shown to not significantly influence the secondary peptide structure. 20 To date the triazole linkage has scarcely been used for peptidesteroid conjugation and only to assemble short apolar tripeptides onto bile acid scaffolds, 24 despite the increasing interest of these type of conjugates in diverse applications such as HIV inhibitors 25,26 and immunogens for vaccine development. 27 In the current work we have designed and synthesized four different scaffolds for peptide dimerization of the GCN4 basic region, which was made possible by optimizing conditions for the CuAAC mediated conjugation of the long, unprotected and functionalized zipper peptides.…”
Section: Q4mentioning
confidence: 99%
“…Based on the advantages above, bile acid dimers, trimers, and tetramers (19)(20)(21)(22)(23)(24)(25)(26) linked with a 1,4-disubsituted 1,2,3-triazole moiety were prepared by Pore s group (Figure 3). [24] Their micellar properties were studied using the hydrophilic dye cresol red (CR) and it was found that all these molecules showed reverse micellar characteristics in nonpolar solvent, [25] and cholic acid-based molecules were able to encapsulate greater amounts of hydrophilic dye than deoxycholic acid-based molecules, which had a direct relationship with the numbers of hydroxy groups. This was the first report to illustrate that dimeric compounds were able to encapsulate a hydrophilic dye in nonpolar solvents, which might arise from the formation of the cis-conformation in the presence of dye (Figure 4).…”
Section: Introductionmentioning
confidence: 99%
“…2 1,2,3-Triazole can serve as a suitable moieties in these drugs since it is stable to metabolic degradation and susceptible to hydrogen bonding beneficial for the affinity with molecular targets and solubility. 3,4 Compounds containing a 1,2,3-triazole moiety show various biological activities such as anti-HIV, 5 anti-microbial, 6 anti-allergic, 7 and selective b3 adrenergic receptor agonist. 8 Ribavirin (Fig.…”
Section: Introductionmentioning
confidence: 99%